Airline schedule and network competitiveness: A consumer-centric approach for business travel. (January 2020) - Nenem, Sukru; Graham, Anne; Dennis, Nigel
Abstract: The aim of this paper is to undertake a comparative analysis of the competitiveness of airline schedules and networks from a business traveller perspective with a particular focus on Europe and travel to and from this continent. A unique and innovative customer-centric model is developed using a passenger survey and airline schedule data to overcome the shortcomings of traditional models that lack the passenger viewpoint. The results show that Austrian Airlines/Vienna airport and Swiss/Zurich airport have the highest quality connections, while the top five competing European hubs are served by the Lufthansa group. The findings provide a significant opportunity to airlines to grow their knowledge and understanding of their competitive position and their ability to offer scheduling convenience to passengers. Highlights: European airline schedules from a business traveller perspective are analysed. A unique innovative customer-centric model is developed using a passenger survey. Austrian/Vienna airport & Swiss/Zurich airport have the highest quality connections. The top five competing European hubs are served by the Lufthansa group.